PENGEMBANGAN MODEL EVALUASI PEMBELAJARAN BAHASA JAWA SMA BERBASIS PENDEKATAN INTEGRATIF-KOMUNIKATIF - Utami, Esti Sudi; Kurniati, Endang (Jurnal Penelitian Pendidikan, 2010)
Evaluation is an important parth of the teaching process. In Javanese language teaching, the focus of evaluation is the students competence in communication. Further more, the evaluation must be able to assest the communicative competence in the test items which to be developed based on communicative-integrative aproach.The goal of this first research is to discribe the developing on evaluation in Javanese learning by the teachers of SMAÃ‚Â  Semarang. The research design is Research and Development. The data are the test series, was made by the teachers of Javanese language in SMA Semarang. The documentation was used to collecting the data. Interractive analyzes was used in this research. The Results are (1) The Javanese learning evaluation is not integrative by means that test items is still in diskret test. (2) The evaluation is not enough communicative (less than 25%). (3) The deviation or less propper not untill 505 more. Keywords : Javanese learning evaluation